A New Method for Quantitative XEDS Tomography of Complex Heteronanostructures. (31st March 2016) - Zanaga, Daniele; Altantzis, Thomas; Polavarapu, Lakshminarayana; Liz‐Marzán, Luis M.; Freitag, Bert; Bals, Sara
Abstract : Reliable quantification of 3D results obtained by X‐ray energy‐dispersive spectroscopy (XEDS) tomography is currently hampered by the presence of shadowing effects and poor spatial resolution. Here, a method is presented which overcomes these problems by synergistically combining quantified XEDS data and high angle annular dark field–scanning transmission electron microscopy tomography. As a proof of principle, the approach is applied to characterize a complex Au/Ag nanorattle obtained through a galvanic replacement reaction. However, the technique that is proposed here is widely applicable to a broad range of nanostructures. Abstract : A new method to quantify X‐ray energy dispersive spectroscopy (XEDS) data in 3D is presented . The synergistic combination of XEDS quantification and Scanning Transmission Electron Microscopy (STEM) tomography enables to overcome the "shadowing" problem and obtain a chemically quantified 3D reconstruction. The technique is used to determine the distribution of elements in a complex Au/Ag nanorattle.